Subclavian mycotic aneurysm caused by Aspergillus flavus in a child with acute lymphoblastic leukemia: a case report - İnceli, Belkıs Hatice; Özdemir, Halil; İnce, Elif; Arga, Gül; Penezoğlu, Döndü Nilay; Çakmaklı, Hasan Fatih; Aknar, Hayreddin; Havan, Merve; Koloğlu, Meltem; Fitöz, Ömer Suat; Özçınar, Evren; Yazıcıoğlu, Levent; et al. (Frontiers in Pediatrics, 2026)
Invasive aspergillosis is a severe opportunistic infection in immunocompromised children, particularly those receiving chemotherapy for hematologic malignancies. We report the case of a 2-year-old girl with acute lymphoblastic leukemia who developed massive hemoptysis during consolidation chemotherapy. Thoracic computed tomography revealed a saccular pseudoaneurysm of the proximal left subclavian artery. Surgical resection and autologous vein graft replacement were performed, and Aspergillus flavus DNA was detected in the resected tissue using Aspergillus-specific polymerase chain reaction. The patient received dual antifungal therapy with liposomal amphotericin B and voriconazole, followed by long-term voriconazole prophylaxis. She made a full recovery. This case highlights the importance of considering angioinvasive aspergillosis in immunocompromised children presenting with hemoptysis and lung lesions. Early recognition and multidisciplinary management are critical to preventing fatal vascular complications.